2024
DOI: 10.1186/s40659-023-00482-x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein dynamics bridge Type-I Interferon response and SARS-CoV-2 replication in peripheral cells

Fiona Limanaqi,
Silvia Zecchini,
Irma Saulle
et al.

Abstract: Background Increasing evidence suggests a double-faceted role of alpha-synuclein (α-syn) following infection by a variety of viruses, including SARS-CoV-2. Although α-syn accumulation is known to contribute to cell toxicity and the development and/or exacerbation of neuropathological manifestations, it is also a key to sustaining anti-viral innate immunity. Consistently with α-syn aggregation as a hallmark of Parkinson's disease, most studies investigating the biological function of α-syn focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“… 95 , 96 Interestingly, a recent study by Limanaqi and colleagues investigated the dynamics of aSyn in peripheral cells during acute SARS-CoV-2 infection in vitro. 97 They found that at later time points post-infection (48 h and beyond), SARS-CoV-2 led to a decrease in SNCA mRNA expression and α-syn immunostaining in lung epithelial cells permissive to productive viral replication. Apart from loss of the protein there is the possibility that antibody binding sites were masked by an unknown folding mechanism of aSyn; however, we used the Syn1 antibody which is well characterized for its broad detection of aSyn species.…”
Section: Discussionmentioning
confidence: 98%
“… 95 , 96 Interestingly, a recent study by Limanaqi and colleagues investigated the dynamics of aSyn in peripheral cells during acute SARS-CoV-2 infection in vitro. 97 They found that at later time points post-infection (48 h and beyond), SARS-CoV-2 led to a decrease in SNCA mRNA expression and α-syn immunostaining in lung epithelial cells permissive to productive viral replication. Apart from loss of the protein there is the possibility that antibody binding sites were masked by an unknown folding mechanism of aSyn; however, we used the Syn1 antibody which is well characterized for its broad detection of aSyn species.…”
Section: Discussionmentioning
confidence: 98%